Astrology in India: A sociological inquiry - Yadav, Nupurnima (London Routledge, 2022)
This book critically examines the larger world of astrology in India, its ubiquity and relationship with religion, caste , gender, class and aspirations
Keywords: religion; Caste; Astrology- India